An Overflow Problem in Network Coding for Secure Cloud Storage - Chen, Yu-Jia; Wang, Li-Chun (IEEE transactions on parallel and distributed systems, 2019)
In this paper, we present the overflow problem of a network coding storage system (NCSS) when the encoding parameters and the storage parameters are mismatched. The overflow problem of the NCSS occurs because the network-coded encryption yields extended coded data, resulting in high storage and processing overhead. To avoid the overflow problem, we propose an overflow-avoidance NCSS scheme that takes account of security and storage requirements in both encoding and storage procedures. We provide the analytical results of the maximum allowable stored encoded data under the perfect secrecy criterion. The design guidelines to achieve high coding efficiency with the lowest storage cost are also presented.